Krisis Komunikasi Digital dan Pengelolaan Reputasi Organisasi di Era Media Sosial: Studi Kasus Pt Timah Tbk dalam Menghadapi Konten Viral Karyawan - Fadhil Muhammad Husain (GLOBAL SCIENTS PUBLISHER, 2026)
The development of social media has changed organizational communication patterns, where the public is not only a recipient of information but also plays an active role in forming opinions and influencing the organization's reputation. This condition causes organizations to face new challenges because an issue originating from an individual can develop into a reputation crisis if it is related to the organization's identity. This study aims to analyze the digital communication crisis of PT Timah Tbk in dealing with viral employee content that has attracted public attention, with a focus on the chronology of the crisis, factors causing virality, the role of social media, Cyber ​​Public Relations strategies, and recommendations for more effective digital crisis communication models. This study uses a descriptive qualitative method with a case study approach through literature analysis, online media coverage, and a review of previous research on digital crisis communication and organizational reputation management. The analysis results show that the PT Timah Tbk crisis occurred due to the dissemination of personal content that was then linked to the organization's image. The virality of the case is influenced by the sensitivity of social issues, public emotional involvement, and the characteristics of social media that enable the rapid dissemination of information. Social media acts as a space for crisis amplification as well as a means for organizational communication in providing clarification. PT Timah Tbk's Cyber ​​PR strategy is carried out through communication responses and collective actions but needs to be strengthened with a more proactive approach. This study recommends a digital crisis communication model that integrates the principles of SCCT, Cyber ​​Relations, and dialogic communication through the stages of issue monitoring, rapid response, public involvement, and trust restoration.